Penerapan Text-To-Speech pada Aplikasi Novel Berbasis Multiplatform - Hairul Fadli; Fajri Profesio Putra (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The development of technology and easy access to the internet has affected reading habits, with digital novel platforms becoming popular as an alternative to reading. However, novelists face obstacles in publishing their works, due to fierce competition in the publishing industry. The proposed solution is to build a multiplatform application system as a platform for novelists to publish their works using the Laravel API. The development method used is Waterfall, which consists of five stages of development. This application will provide features that facilitate interaction between novelists and readers, such as likes, comments, and uniquely there is a feature to listen to novels via voice for users who prefer to listen rather than read, with a text-to-speech system. In addition, the app allows novelists to build a stronger fan base. This research aims to provide a practical and efficient platform for novelists to write, edit and publish their works online through the features provided in the application. System testing was carried out using the System Usability Scale (SUS) method to get a score of 79.5 including the Good category with grade scale B. The programming language used in the development of this application is Flutter, which allows the creation of multiplatform applications with responsive and consistent performance on various devices.